Quality of relationships between residential staff and youth: A systematic review - Pinheiro, M. (2023)
Regardless of the type of residential care context, entering in care is an impactful event that involves the separation of young people from their relatives, as well as the need to adapt to a new context. This adaptation might be facilitated by the quality of relationships with professionals in these settings, which in turn may positively impact young people’s psychological adjustment. Purpose: The current systematic review aims to identify the factors that might be associated with quality relationships in residential homes (i.e., generalist care, therapeutic care, juvenile justice settings) at different ecological levels. Method: A systematic electronic search was conducted in eight databases: Academic Search Complete, APA PsycArticles, APA PsycINFO, Psychology and Behavioral Sciences Collection, ERIC, MEDLINE, Web of Science and Scopus, using a combination of words related with quality relationship, residential care, children, and adolescent. Based on the PRISMA statement, 919 manuscripts were yielded, and thirteen studies met the inclusion criteria. Results: Child (e.g., gender or age), professionals (e.g., professionals’ characteristics, behaviors, and skills), organizational (e.g., Ratios of children to professionals on staff) and cross-cutting factors (e.g., time spent together, length of relationship) were found to be associated with quality relationships between professionals and young people in care. Discussion: The residential care settings should be able to provide appropriate resources and services which address young people’s complex needs. Practical implications are discussed.